2022
DOI: 10.3390/microorganisms10040778
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Bloodstream Infection due to a KPC-Producing Klebsiella Pneumoniae Resistant to Imipenem/Relebactam in a Hematological Patient

Abstract: Novel carbapenem-β-lactamase inhibitor combination, imipenem/relebactam (IMI-REL), has been recently approved for treatment of infections with limited or no alternative treatment options. In this study, we described the emergence of the IMI-REL-resistance in a KPC-producing Klebsiella pneumoniae (KPC-Kp) strain collected from a hematological patient with no evidence of prior colonization. Interestingly, IMI-REL-resistance was associated with meropenem/vaborbactam (MER-VAB) cross-resistance but was not associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Moreover, the same mechanisms of K. pneumoniae resistance to combinations of imipenem with relebactam were also described in vivo. It was reported that the K. pneumoniae clinical isolate initially susceptible to imipenem/relebactam acquired resistance to this combination during antimicrobial therapy of a hematology patient with a bloodstream infection [ 32 ]. The resistance mechanism of this K. pneumoniae isolate was associated with an increased bla KPC-3 copy number and disruptions of porins ( OmpK 35 and OmpK 36).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the same mechanisms of K. pneumoniae resistance to combinations of imipenem with relebactam were also described in vivo. It was reported that the K. pneumoniae clinical isolate initially susceptible to imipenem/relebactam acquired resistance to this combination during antimicrobial therapy of a hematology patient with a bloodstream infection [ 32 ]. The resistance mechanism of this K. pneumoniae isolate was associated with an increased bla KPC-3 copy number and disruptions of porins ( OmpK 35 and OmpK 36).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from purified cultures of K. pneumoniae using DNeasy Blood&Tissue Kit (Qiagen, Basel, Switzerland) by following the manufacturer’s instructions and further cleaned up with AMPure XP magnetic beads (Beckman Coulter). Whole genome analysis was performed as previously described [ 20 ]. Briefly, bacterial genomes libraries were prepared using Illumina DNA Prep paired-end kit and sequenced by the Illumina iSeq 100 platform (iSeq Reagent Kit v2, Illumina, San Diego, CA, USA) using iSeq Reagent kit v2 with 2 × 150 paired-end reads.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from purified cultures of Klebsiella pneumoniae using DNeasy Blood&Tissue Kit (Qiagen, Basel, Switzerland), following the manufacturer’s instructions, and was further cleaned with AMPure XP magnetic beads (Beckman Coulter, Krefeld, Germany). Whole-genome analysis was performed as previously described [ 28 ]. Briefly, bacterial genomes were sequenced using the Illumina iSeq 100 platform (iSeq Reagent Kit v2, Illumina, San Diego, CA, USA) with an iSeq Reagent kit v2 and 2 × 150 paired-end reads after using Illumina DNA Prep paired-end library preparation.…”
Section: Methodsmentioning
confidence: 99%
“…Porin genes were manually investigated using BLAST analysis against a reference protein (OmpK35 [O87753], OmpK36 [D6QLX8] and OmpK37 [S5UDN6]), and prophage regions within the KPC-Kp genome were assessed using PHASTER ( , accessed on 9 October 2022). The phylogenetic tree was generated using core genome SNP analysis as previously described [ 28 ]. SNPs and insertion-deletions (Indels) between CAZ-AVI and/or MER-VAB and/or IMI-REL resistant genomes were investigated as previously described [ 22 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation